Shifts in prokaryotic communities and giant sulphur-oxidising bacteria in response to salmon aquaculture in sub-Antarctic marine sediments - Carlos P. Aranda; Alejandro H. Buschmann; Alejandro Bisquertt; Daniel Vega; Alex R. González; Mauricio Quiroz (Marine Pollution Bulletin, 2026)

Open-sea cultivation of gracilarioids: The current state of Gracilaria chilensis cultivation in Chile - Alejandro H. Buschmann; Sara Usandizaga (Journal of Applied Phycology, 2025)

Punctaria latifolia as a new source of alginate: structural characteristics and biological activity - Ailen M. Poza; Carolina Fernández; Fabián Martínez-Gómez; M. Emilia Croce; Virginia Lezcano; Alejandro H. Buschmann; Marcelo A. Villar (Journal of Applied Phycology, 2025)

The giant kelp holdfasts macroinvertebrate assemblages: Towards benthic management and conservation using alpha and beta diversity in Northern Patagonia - Ángela M. Baldrich; Camilo Rodríguez-Villegas; Alejandro H. Buschmann (Regional Studies in Marine Science, 2024)

Giant kelp recruitment declines and changes in understory algae in a sub-Antarctic urban ecosystem - Julieta Kaminsky; María Bagur; Alicia Boraso; Mariano Rodríguez; Alejandro H. Buschmann; María Liliana Quartino; Irene R. Schloss (Hydrobiologia, 2024)

Diverse inorganic carbon uptake strategies in Antarctic seaweeds: Revealing species-specific responses and implications for Ocean Acidification - Pamela A. Fernández; Charles D. Amsler; Catriona L. Hurd; Patricio A. Díaz; Juan Diego Gaitán-Espitia; Erasmo C. Macaya; Andreas Schmider-Martínez; Ignacio Garrido; Pedro Murúa; Alejandro H. Buschmann (Science of The Total Environment, 2024)

Performance of the estuarine alga Punctaria latifolia (Phaeophyceae) under different abiotic culture conditions - Ailen M. Poza; Carolina Fernández; M. Emilia Croce; M. Cecilia Gauna; Alejandro H. Buschmann (Journal of Applied Phycology, 2024)

Feasibility of bioplastic production using micro- and macroalgae- A review - Muthiyal Prabakaran Sudhakar; Rahulkumar Maurya; Sanjeet Mehariya; Obulisamy Parthiba Karthikeyan; Gopal Dharani; Kulanthiyesu Arunkumar; Sandra V. Pereda; María C. Hernández-González; Alejandro H. Buschmann; Arivalagan Pugazhendhi (Environmental Research, 2024)

Giant kelp (Macrocystis pyrifera) morphological and reproductive strategies in two contrasting sub-Antarctic forests - Julieta Kaminsky; María Bagur; Irene Ruth Schloss; Soledad Diodato; Mariano Rodríguez; Alejandro H. Buschmann; María Liliana Quartino (Marine Biology, 2024)

Seaweed blue carbon: Ready? Or Not? - Rod Fujita; Simona Augyte; Jennifer Bender; Poppy Brittingham; Alejandro H. Buschmann; Max Chalfin; Jamie Collins; Kristen A. Davis; John Barry Gallagher; Rebecca Gentry; Rebecca L. Gruby; Kristin Kleisner; et al. (Marine Policy, 2023)

The influence of ammonium to nitrate ratio on the thermal responses of early life stages of the giant kelp Macrocystis pyrifera - Pamela A. Fernández; Bárbara Labbé; Juan D. Gaitán-Espitia; Catriona L. Hurd; Ellie R. Paine; Anusuya Willis; Craig Sanderson; Alejandro H. Buschmann (Algal Research, 2023)

Overview of global Gracilaria production, the role of biosecurity policies and regulations in the sustainable development of this industry - Vaibhav A. Mantri; Cicilia S. B. Kambey; Elizabeth J. Cottier‐Cook; Sara Usandizaga; Alejandro H. Buschmann; Ik Kyo Chung; Tao Liu; Calvyn F. A. Sondak; Zizhong Qi; Phaik Eem Lim; Nguyen Van Nguyen (Reviews in Aquaculture, 2023)
Gracilaria aquaculture is one of the fastest‐growing sectors, contributing to 10.5% of the global seaweed feed‐stock supply chain in 2019. It predominantly caters to food‐grade agar, animal feed and non‐food sector applications viz. biotechnology, biomedical and pharmaceuticals. It has witnessed a rapid expansion triggered by increased demand due to commodity trade. Biosecurity‐related issues are the key factors constraining its expansion, but are seldom addressed. The global gracilarioids aquaculture is dominated by China and other Asian countries, namely the Republic of Korea, Indonesia, the Philippines and Vietnam. This paper provides an assessment of their national biosecurity capacity, including current risk management strategies, policies and the implementation of existing regulations. It also highlights specific gaps in national policies and regulations, which can be addressed to improve their health management systems. Biosecurity management strategies, such as the provision of clear regulatory guidance, mechanisms for notifying disease and pest outbreaks, movement of live seaweed, risk assessment, stakeholder incentivisation and certification are recommended. Further, insights into the impending biosecurity measures to the emerging countries in this domain namely India and Malaysia are discussed. We suggest, implementing a uniform format of global integrated biosecurity measures across the Gracilaria aquaculture industry, but this requires organisational, operational and procedural changes, coupled with a cross‐sectoral application of risk analysis protocols. Despite one of the important seaweed aquaculture taxa, an overview of Gracilaria production, the role of biosecurity policy and regulation in the sustainable development of this industry was still lacking, this is the first global effort in this direction.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Physiological stress modulates epiphyte (Rhizoclonium sp.)-basiphyte (Agarophyton chilense) interaction in co-culture under different light regimes - Pablo P. Leal; Johana Ojeda; Carolina Sotomayor; Alejandro H. Buschmann (Journal of Applied Phycology, 2020)

Concise reviews of seaweeds of current and future commercial interest - Alan T. Critchley; Leonel Pereira; Alejandro H. Buschmann; Anicia Q. Hurtado; Michael A. Borowitzka (Journal of Applied Phycology, 2020)

Effect of temperature variation in Agarophyton chilensis: contrasting the response of natural and farmed populations - Sara Usandizaga; Carolina Camus; José Luis Kappes; Marie-Laure Guillemin; Alejandro H. Buschmann (Journal of Applied Phycology, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Overview of 3 year precommercial seafarming of Macrocystis pyrifera along the Chilean coast - Carolina Camus; Javier Infante; Alejandro H. Buschmann (Reviews in Aquaculture, 2018)
Chile is one of the main producers of seaweeds in the world; however, most of the production comes from harvesting natural beds and only 2.4% from cultures, dominated by the agarophyte Gracilaria chilensis . One of the most exploited resources is the giant kelp Macrocystis pyrifera , which is sold fresh for abalone feed and dry for alginate extraction. Recently, new possible markets are developing for this species, for example human consumption and biofuel/chemical production that could increase the demand and justify the development of a commercial cultivation system. The objective of this work was to present the recent development of the seafarming of M. pyrifera in Chile, focusing on the fundamental determinants of productivity in cultivated systems and the identification of the binding constraints to productivity. Three experimental plots (up to 21 Ha) were designed and deployed in three study areas (Caldera in northern Chile and Quenac and Ancud in southern Chile) to test different environmental conditions. During a period of 3 years, sporophytes produced in an indoor hatchery were deployed monthly, at different densities, and followed until harvest. Environmental parameters and biomass were monitored on a monthly basis. Our findings demonstrate the feasibility of Macrocystis seafarming on a large scale in Chile. Important differences in yield were observed between the study areas associated with either environmental physical or biological factors, such as the presence of herbivores. Our best production cycle reached 124 WMT Ha −1 month −1 in southern Chile, and the worst, less than 20 WMT Ha −1 month −1 in northern Chile. Finally, some direct and indirect constrains were encountered, including seeding season and depth, and the presence of pests and diseases, that are discussed.

Unpacking factors influencing antimicrobial use in global aquaculture and their implication for management: a review from a systems perspective - Patrik J. G. Henriksson; Andreu Rico; Max Troell; Dane H. Klinger; Alejandro H. Buschmann; Sonja Saksida; Mohan V. Chadag; Wenbo Zhang (Sustainability Science, 2018)

Effects of light, temperature and stocking density on Halopteris scoparia growth - Rita F. Patarra; Ana S. Carreiro; Anna A. Lloveras; Maria H. Abreu; Alejandro H. Buschmann; Ana I. Neto (Journal of Applied Phycology, 2017)

Bioremediation potential, growth and biomass yield of the green seaweed, Ulva lactuca in an integrated marine aquaculture system at the Red Sea coast of Saudi Arabia at different stocking densities and effluent flow rates - Yousef S. Al‐Hafedh; Aftab Alam; Alejandro H. Buschmann (Reviews in Aquaculture, 2015)
Growth, production and biofiltration rates of seaweed, Ulva lactuca were investigated at two stocking densities (3 kg and 6 kg m −2 ) and two effluent flow rates (5.4 and 10.8 m 3 day −1 ) to optimize an integrated mariculture system at Saudi Red Sea coast. effluents from fish‐rearing tank, stocked with 200 kg fish ( Oreochromis spilurus ), fed to six seaweed tanks via sedimentation tank. Fish growth (weight gain 1.75 g fish day −1 ), net production (NP, 10.16 kg m −3 ) and survival (94.24%) were within acceptable limits. Ulva showed significantly higher ( F = 62.62, d.f. 3, 35; P SGR = 5.78% vs. 2.55% at lower flow and 10.60% vs. 6.26% at higher flow). Biomass yield of Ulva at low‐ and high‐stocking densities (111.11 and 83.2 g wet wt m −2 day −1 , respectively) at low flow and (267.44 and 244.19 g wet wt m −2 day −1 , respectively) at high flow show that high flow rate and lower density favoured growth. Removal rates of total ammonia nitrogen ( TAN ) (0.26–0.31 g m −2 day −1 ) and phosphate phosphorus (0.32–0.41 g m −2 day −1 ) by U. lactuca were not significantly different ( F = 1.9, d.f. 3, 59; P = 0.1394 for TAN and F = 0.29, d.f. 3, 59; P = 0.8324 for phosphates) at both the flow rates and stocking densities. Results show that the effluent flow rate has significant impact over the performance of the seaweed than stocking density.

Antimicrobial resistance and antimicrobial resistance genes in marine bacteria from salmon aquaculture and non‐aquaculture sites - Syed Q. A. Shah; Felipe C. Cabello; Trine M. L'Abée‐Lund; Alexandra Tomova; Henry P. Godfrey; Alejandro H. Buschmann; Henning Sørum (Environmental Microbiology, 2014)
Summary Antimicrobial resistance ( AR ) detected by disc diffusion and antimicrobial resistance genes detected by DNA hybridization and polymerase chain reaction with amplicon sequencing were studied in 124 marine bacterial isolates from a C hilean salmon aquaculture site and 76 from a site without aquaculture 8 km distant. Resistance to one or more antimicrobials was present in 81% of the isolates regardless of site. Resistance to tetracycline was most commonly encoded by tetA and tetG ; to trimethoprim, by dfrA1, dfrA5 and dfrA12 ; to sulfamethizole, by sul1 and sul2 ; to amoxicillin, by bla TEM ; and to streptomycin, by strA‐strB . Integron integrase intl1 was detected in 14 sul1 ‐positive isolates, associated with aad9 gene cassettes in two from the aquaculture site. intl2 Integrase was only detected in three dfrA1 ‐positive isolates from the aquaculture site and was not associated with gene cassettes in any. Of nine isolates tested for conjugation, two from the aquaculture site transferred AR determinants to E scherichia coli . High levels of AR in marine sediments from aquaculture and non‐aquaculture sites suggest that dispersion of the large amounts of antimicrobials used in Chilean salmon aquaculture has created selective pressure in areas of the marine environment far removed from the initial site of use of these agents.

Ecophysiological plasticity of annual populations of giant kelp (Macrocystis pyrifera) in a seasonally variable coastal environment in the Northern Patagonian Inner Seas of Southern Chile - Alejandro H. Buschmann; Sandra V. Pereda; Daniel A. Varela; Juan Rodríguez-Maulén; Alejandra López; Luis González-Carvajal; Marcela Schilling; Eduardo A. Henríquez-Tejo; María C. Hernández-González (Journal of Applied Phycology, 2014)

Generation and application of monoclonal antibodies against Rift Valley fever virus nucleocapsid protein NP and glycoproteins Gn and Gc - Susanne Jäckel; Martin Eiden; Malte Dauber; Anne Balkema-Buschmann; Alejandro Brun; Martin H. Groschup (Archives of Virology, 2014)

Antimicrobial use in aquaculture re‐examined: its relevance to antimicrobial resistance and to animal and human health - Felipe C. Cabello; Henry P. Godfrey; Alexandra Tomova; Larisa Ivanova; Humberto Dölz; Ana Millanao; Alejandro H. Buschmann (Environmental Microbiology, 2013)
Summary The worldwide growth of aquaculture has been accompanied by a rapid increase in therapeutic and prophylactic usage of antimicrobials including those important in human therapeutics. Approximately 80% of antimicrobials used in aquaculture enter the environment with their activity intact where they select for bacteria whose resistance arises from mutations or more importantly, from mobile genetic elements containing multiple resistance determinants transmissible to other bacteria. Such selection alters biodiversity in aquatic environments and the normal flora of fish and shellfish. The commonality of the mobilome (the total of all mobile genetic elements in a genome) between aquatic and terrestrial bacteria together with the presence of residual antimicrobials, biofilms, and high concentrations of bacteriophages where the aquatic environment may also be contaminated with pathogens of human and animal origin can stimulate exchange of genetic information between aquatic and terrestrial bacteria. Several recently found genetic elements and resistance determinants for quinolones, tetracyclines, and β‐lactamases are shared between aquatic bacteria, fish pathogens, and human pathogens, and appear to have originated in aquatic bacteria. Excessive use of antimicrobials in aquaculture can thus potentially negatively impact animal and human health as well as the aquatic environment and should be better assessed and regulated.

Can giant kelp ( Macrocystis pyrifera ) forests enhance invertebrate recruitment in southern Chile? - Viviana Almanza; Alejandro H. Buschmann; María C. Hernández-González; Luís A. Henríquez (Marine Biology Research, 2012)

Experiments on an integrated aquaculture system (seaweeds and marine fish) on the Red Sea coast of Saudi Arabia: efficiency comparison of two local seaweed species for nutrient biofiltration and production - Yousef S. Al‐Hafedh; Aftab Alam; Alejandro H. Buschmann; Kevin M. Fitzsimmons (Reviews in Aquaculture, 2012)
Seaweeds absorb inorganic nutrient wastes from mariculture and reduce their undesirable environmental effects. Mariculture in Saudi Arabia is increasing rapidly, thus, to exploit aquaculture wastes and to reduce coastal pollution risks, local seaweeds were cultured using mariculture effluents in integration on the Red Sea coast. The aim of the present study was to test integrated aquaculture of seaweed and marine fish ( Oreochromis spilurus ) for the first time in Saudi Arabia and to determine the seaweeds, Ulva lactuca and Gracilaria arcuata , biomass production and inorganic nutrient bioremediation capabilities. Results showed that G. arcuata grew at a significantly higher rate (2.71% wet weight day −1 ) than U. lactuca (1.77% wet weight day −1 ). The biomass yield (42.38 g wet weight m −2 day −1 ) and net yield (91.11 g wet weight day −1 ) of G. arcuata were also significantly higher than U. lactuca (27.39 g wet weight m −2 day −1 and 58.89 g wet weight day −1 , respectively). Gracilaria arcuata removed 0.45 g m −2 day −1 of total ammonia nitrogen (TAN) with 80.15% removal efficiency and 1.03 g m −2 day −1 of soluble phosphate with 41.06% efficiency. Ulva lactuca removed 0.42 g m −2 day −1 of TAN with 83.06% removal efficiency and 1.07 g m −2 day −1 of soluble phosphate with 41.11% efficiency. Total tissue carbon of both species reached 25.1–26.9% and nitrogen content reached 3.0–3.2% of dry weight. The C/N ratio for both seaweeds was G. arcuata has relatively higher growth potential.

A pilot-scale study of the vegetative propagation and suspended cultivation of the carrageenophyte alga Gigartina skottsbergii in southern Chile - Renato Westermeier; David J. Patiño; Pedro Murúa; Juan C. Quintanilla; Juan Correa; Alejandro H. Buschmann; Ismael Barros (Journal of Applied Phycology, 2012)

Opportunities and challenges for the development of an integrated seaweed-based aquaculture activity in Chile: determining the physiological capabilities of Macrocystis and Gracilaria as biofilters - Alejandro H. Buschmann; Daniel A. Varela; María Carmen Hernández-González; Pirjo Huovinen (Journal of Applied Phycology, 2008)

Long Term Variability in the Structure of Kelp Communities in Northern Chile and the 1997–98 ENSO - Julio A. Vásquez; J. M. Alonso Vega; Alejandro H. Buschmann (Journal of Applied Phycology, 2006)

Reproduction strategies of Macrocystis pyrifera (Phaeophyta) in Southern Chile: The importance of population dynamics - Alejandro H. Buschmann; Cristina Moreno; Julio A. Vásquez; María C. Hernández-González (Journal of Applied Phycology, 2006)

Farming of the Giant Kelp Macrocystis Pyrifera in Southern Chile for Development of Novel Food Products - Alfonso Gutierrez; Tomás Correa; Verónica Muñoz; Alejandro Santibañez; Roberto Marcos; Carlos Cáceres; Alejandro H. Buschmann (Journal of Applied Phycology, 2006)

Cultivation of Gigartina skottsbergii (Gigartinales, Rhodophyta): Recent advances and challenges for the future - Alejandro H. Buschmann; Juan A. Correa; Renato Westermeier; María A. Paredes; Diego Aedo; P. Potin; Gesica Aroca; Jessica Beltrán; María C. Hernández-González (Journal of Applied Phycology, 2001)

Healing and regeneration responses in Gigartina skottsbergii (Rhodophyta, Gigartinales): optimization of vegetative propagation for cultivation - Juan A. Correa; Jessica Beltrán; Alejandro H. Buschmann; Renato Westermeier (Journal of Applied Phycology, 1999)

Recent advances in the understanding of the biological basis for Gigartina skottsbergii (Rhodophyta) cultivation in Chile - Alejandro H. Buschmann; Juan A. Correa; Renato Westermeier (Hydrobiologia, 1999)

Ceramialean epiphytism in an intertidal Gracilaria chilensis (Rhodophyta) bed in southern Chile - Alejandro H. Buschmann; Claudia A. Retamales; Claudia Figueroa (Journal of Applied Phycology, 1997)